Проблемы неэффективного использования бюджетных средств - Бойко, А.; Шевченко, М.В. (Культура народов Причерноморья, 2014)
В условиях современной экономической ситуации Украины вопрос эффективности
использования государственных средств приобретают особую актуальность, поскольку большинство
общегосударственных проблем нуждается в более рациональном использовании бюджетных средств. В умовах сучасної економічної ситуації України питання ефективності використання
державних коштів набувають особливу актуальність, оскільки більшість загальнодержавних проблем
потребують раціональнішого використання бюджетних коштів. In the conditions of modern economic situation of Ukraine the question of efficiency of the use of
state facilities is acquired the special actuality, as most national problems need more rational use of budgetary
facilities.
There is a necessity to probe problems, related to the uneffective use of budgetary facilities. To set reasons of
this phenomenon and negative factors which make basis of budgetary offences. To offer the ways of decision of
problem with the purpose of settlement of situation and providing of the rational use of the budgetary settings.
The dynamics of volumes of the uneffective utillized facilities testifies to the considerable lacks of functioning of
the budgetary system, its low efficiency and effectiveness.
Unfortunately, in the field of state finances until now the clear system of effective measures is not adjusted for
prevention of opaque and uneffective procedures of the use of state facilities.